Demographic, physical and mental health assessments in the adolescent brain and cognitive development study: Rationale and description. (August 2018) - Barch, Deanna M.; Albaugh, Matthew D.; Avenevoli, Shelli; Chang, Linda; Clark, Duncan B.; Glantz, Meyer D.; Hudziak, James J.; Jernigan, Terry L.; Tapert, Susan F.; Yurgelun-Todd, Debbie; Alia-Klein, Nelly; Potter, Alexandra S.; et al.
Abstract: The Adolescent Brain and Cognitive Development (ABCD) Study incorporates a comprehensive range of measures assessing predictors and outcomes related to both mental and physical health across childhood and adolescence. The workgroup developed a battery that would assess a comprehensive range of domains that address study aims while minimizing participant and family burden. We review the major considerations that went into deciding what constructs to cover in the demographics, physical health and mental health domains, as well as the process of selecting measures, piloting and refining the originally proposed battery. We present a description of the baseline battery, as well as the six-month interim assessments and the one-year follow-up assessments. This battery includes assessments from the perspectives of both the parent and the target youth, as well as teacher reports. This battery will provide a foundational baseline assessment of the youth's current function so as to permit characterization of stability and change in key domains over time. The findings from this battery will also be utilized to identify both resilience markers that predict healthy development and risk factors for later adverse outcomes in physical health, mental health, and substance use and abuse.